2003
DOI: 10.1088/0960-1317/13/5/304
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical analysis of micromachined gas sensors

Abstract: In this paper, we present a complete thermomechanical study of a micromachined gas sensor substrate. The work has been carried out combining coupled electrothermomechanical three-dimensional finite element modelling simulations with electrical, infrared thermography and interferometric microscopy experimental measurements. The performances predicted by simulations, such as the power consumption (heating efficiency in air of 5.7 • C mW −1), the time response (19 ms), the membrane deflection during operation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 19 publications
3
66
0
Order By: Relevance
“…44. The linear behavior along the bridges changes into a parabolic one across the MHP, and have been observed in prior publications 60,64 . The maximum temperature, temperature profile, and gradient are affected by the bridge width.…”
Section: Resultssupporting
confidence: 65%
“…44. The linear behavior along the bridges changes into a parabolic one across the MHP, and have been observed in prior publications 60,64 . The maximum temperature, temperature profile, and gradient are affected by the bridge width.…”
Section: Resultssupporting
confidence: 65%
“…This is likely due to the reaction with the passivation layer and the oxidation/reoxidation cycles taking place during the fabrication process. According to Puigcorbé et al, 11 Ti from the adhesion layer and N from the Si 3 N 4 passive layer probably migrate into the Pt film, reaching the Pt surface and modifying the heater electrical resistivity. Additionally, the intrinsic and thermal stresses of the Ti/Pt layer led to formation of hillocks on the heater surface, which has previously been observed for annealing temperatures above 650°C.…”
Section: Methodsmentioning
confidence: 99%
“…Due to poor stability showed by polysilicon heaters formerly used in micro hotplates when operated at temperatures higher than 500°C (Puigcorbé et al 2003), a doped bulk crystalline silicon slab has been chosen for the realization of the radiating elements. Recent investigations (Spannhake et al 2006) have demonstrated high temperature realizations of silicon micro hot-plates using direct Joule heating of the SOI layer to attain temperatures close to 1,000°C.…”
Section: Device Fabricationmentioning
confidence: 99%